Leveraging sequence‐based faecal microbial community survey data to identify alterations in gut microbiota among patients with Parkinson's disease. (15th September 2020) - Ji, Tianyi; Huang, Hongyan; Liu, Jiaxuan; Peng, Tian; Zhou, Xiazhu; Tan, Qin; Yuan, Jiaguo; Hua, Huan; Ding, Songtao; Liu, Handeng
Abstract: Parkinson's disease is a common degenerative disease of the elderly. Although the majority of studies have focused on the central nervous system (CNS) features of Parkinson's disease, recent findings suggest there is a functional link between the gut microbiome and the hallmarks of the disease. PubMed, Web of Science, EMBASE and other Chinese and English databases were searched for relevant literature. Studies on changes to intestinal microbiota in Parkinson's patients were retrieved and systematically reviewed. Quality filtering, clustering and species annotation were performed on 16s sequencing raw data from retrieved studies to achieve comparability across studies. Alpha‐diversity indices and a random effect model were used to analyse significantly altered microbiota. A total of nine studies were included in this retrospective analysis, four of which contained raw data. Alpha diversity was significantly different between control and Parkinson's disease patients in two of the four studies. Using the raw data from four individual studies, we observed differences in the phlya Bacteroidetes and Actinobacteria . Additionally, differences were observed between control and Parkinson's disease patients at the level of family ( Prevotellacaea and Lactobacillaceae ) and genus ( Bifidobacterium and Clostridium ). This study confirmed that changes in the microbiome are a consistent feature of Parkinson's disease patients and, therefore, may contribute to the onset of disease. Abstract : By processing the 16sRNA data sequenced in different studies, significant changes in the bacteria were found. And there are summary of the mechanisms of gut microbiota contributions to PD.